Capillary pressure during and after incremental venous pressure elevation in man. - Mahy, I R (1995)
1. The relationship between capillary pressure and venous pressure was investigated during incremental venous pressure elevation in seven healthy volunteers. Pressure was measured simultaneously at the apex of finger nailfold capillaries and in the dorsal vein of the ipsilateral hand. Elevation of venous pressure was accomplished by inflation of a sphygmomanometer cuff around the upper arm. 2. As venous pressure rose, apical capillary pressure (Pc) approached venous pressure (Pv). For changes in Pv greater than 20 mmHg, the increment in Pc was invariably less than the increment in Pv. 3. Above a cuff pressure of 20 mmHg, capillary pulse pressure amplitude (CPPA) tended to decline. At 50 mmHg cuff pressure, CPPA was lower than at baseline for all subjects. At baseline, CPPA was 4.2 +/- 2.0 mmHg (mean +/- S.D.) and at 50 mmHg it was 2.3 +/- 1.1 mmHg (P = 0.02). 4. In the period between 1 and 6 min following cuff release, both Pc and CPPA were lower than at baseline. (At baseline, Pc was 16.1 +/- 2.3 mmHg and following cuff release it was 11.2 +/- 1.5 mmHg (P = 0.02). At baseline, CPPA was 4.2 +/- 2.0 mmHg and following cuff release it was 1.8 +/- 1.1 mmHg (P = 0.03).) 5. Estimated changes in the ratio of pre- to postcapillary resistance (Ra/Rv), using arterial blood pressure (Pa) measured in the contralateral arm, and taking (Pa-Pc)/(Pc-Pv) to approximate to Ra/Rv, closely mirrored changes in CPPA.(ABSTRACT TRUNCATED AT 250 WORDS)